Cooling Rates of Chondrules after Lightning Discharge in Solid-rich Environments - Hiroaki Kaneko; Kento Sato; Chihiro Ikeda; Taishi Nakamoto (The Astrophysical Journal, 2023)
Among the several candidate models for chondrule formation, the lighting model has been recognized to be less likely than the other two major models, shock-wave heating and planetesimal collision. It might be because we have believed that the lightning model predicts cooling rates of chondrules that are too fast to reproduce their textures with the assumption that the discharge channels must be optically thin. However, the previous works revealed that the buildup of a strong electric field to generate the lightning in protoplanetary disks requires the enhancement of the solid density. Moreover, some properties of chondrules indicate their formation in environments with such a high solid density. Therefore, the discharge channels may be optically thick, and the lightning model can potentially predict the proper cooling rates of chondrules. In this study, we reinvestigate the cooling rates of chondrules produced by the lightning in the solid-rich environments considering the radiative transfer and the expansion of the hot channel. Chondrules must interact dynamically with the surrounding gas and dust via the drag force. We consider two limiting cases for the dynamics of chondrules: the drag force is ignored in the first case, and chondrules are completely coupled with their surroundings in the second case. In both cases, the lightning model predicts the proper cooling rates of chondrules under the optically thick conditions with high solid enhancement. Therefore, the lightning model is worth further investigation to judge its reliability as the source of chondrule formation.